Local Food Culture Festival Management Model in Papua - Fitriani, Fitriani; Betaubun, Martha; Suhendra, Fajar Arfid (Technium Social Sciences Journal, 2024)
This research is a continuation of research and service as well as articles presented in international seminars and Bapenas FGDs. Research, PkM, International Seminars and FGDs from BAPENAS that have been carried out provide an illustration that Papua has great potential in local food, especially those made from sago. This is supported by the availability of sago forests and people who are starting to understand the preservation of sago forests and people who are creative in processing sago food in various preparations. However, the community has not yet found the right form to promote local food well and have a big impact. Conditions like this provide an opportunity for the government and academics to play a role in formulating the right strategy and realizing it in a major activity that can be known by many people nationally and internationally. One of the activities that can support the condition of people who are in this position is the government implementing a Local Food Culture Festival which is held on a scheduled schedule every year. This research aims to create a management model for local food culture festivals which is carried out in 2 (two) stages, namely Phase I (2023) sharing knowledge of the research team with festival management experts at UNY as well as concocting a suitable or appropriate form for festival management in Merauke Regency, as well as Benchmarking at several Cultural Festivals organized by the Yogyakarta Special Region Government (DIY) in September 2023, and Phase II (2024) the research team will carry out education and FGDs for 3 days for the Tourism and Culture Offices of Merauke Regency and South Papua Province as well as the candidates festival participants from the local food business community. The results of this research found that organizing a festival requires high synergy from the organizing team itself and from the government and sponsors. The most important thing is that it is necessary to carry out a survey or initial analysis of the festival theme which can describe the vision of the activities, potential and targets to be achieved by the festival. The budget and activity plan must be determined well in advance so that it can be included in the annual expenditure of sponsors or local governments. The selection of the organizing team must also be a professional team or a combination of a professional team and the sponsor, so that the implementation can go according to plan. Apart from that, the community must also be involved or empowered to participate. What is different about festivals held in the Papua region is the very dominant role of local communities involved in helping to improve the economy of the local population and promoting existing Papuan culture, apart from that there is still a lack of third parties who are willing to sponsor festival activities in Papua, especially Papuan cultural and local food festival.